2009
DOI: 10.1088/0268-1242/24/9/095020
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion behaviour of vanadium in GaN thin films studied by secondary ion mass spectrometry

Abstract: A sandwiched multi-structure made of alternatively undoped and vanadium (V) doped GaN layers was grown on SiN-treated (0 0 0 1) sapphire substrates by atmospheric pressure metal organic chemical vapour deposition (AP-MOCVD). The V diffusion in GaN has been investigated in the temperature range of 1000-1100 • C by using secondary ion mass spectroscopy. The diffusion coefficients were obtained through a data-fitting program based on Fick's first law. The results suggest that V diffuses faster near the GaN/sapphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This brings about a degradation of the surface. Furthermore, during the annealing, diffusion of vanadium to the surface starts [9], so the density of vanadium atoms located at the Table 1 The FWHM of (0 0 0 2) and (1 0 1 5) diffraction planes of vanadium-doped samples with 2 and 4 sccm. surface increases, which can cause contamination of the surface by the vanadium element [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This brings about a degradation of the surface. Furthermore, during the annealing, diffusion of vanadium to the surface starts [9], so the density of vanadium atoms located at the Table 1 The FWHM of (0 0 0 2) and (1 0 1 5) diffraction planes of vanadium-doped samples with 2 and 4 sccm. surface increases, which can cause contamination of the surface by the vanadium element [13].…”
Section: Resultsmentioning
confidence: 99%
“…It is also necessary for the activation of doped ions such as Mg acceptors in GaN [7,8]. Recently, a study on the diffusion of vanadium in the GaN has been made [9]. In this study, several samples formed by the structure GaN/GaN:V has been annealed at different temperatures: 1000, 1025, 1050, 1075 1C (30 min) and 1100 1C (10 min).…”
Section: Introductionmentioning
confidence: 99%
“…The clear peak at 200-300 nm visible in the profile of figure 4 (annealing at 850 • C) is missing in the profile of figure 5 (annealing at 950 • C). As it has been shown that electron irradiation induced [35], N [36], Mg [37], Mg ( ) [38], Si [39], V [40], Er [41] and Pt [42]. The data of Au [43] have been excluded from the figure as they are available only for lower temperatures (300-400 • C).…”
Section: Be Migration and Interaction With Implantation Induced Defec...mentioning
confidence: 99%
“…Arrhenius plot of available GaN diffusion data excluding H and its isotopes. Present results , Be (•)[35], N[36], Mg[37], Mg ( )[38], Si[39], V[40], Er[41] and Pt[42]. The data of Au[43] have been excluded from the figure as they are available only for lower temperatures (300-400 • C).…”
mentioning
confidence: 99%
“…3(a)) by Nudged Elastic Band (NEB) method, 23 which is smaller than that of V diffusion in GaAs (1.51 eV) 16 and GaN (2.9 ± 0.4 eV). 24 Seen from Fig. 1, a V atom at the T Ga site can kicks a Ga atom out of its equilibrium position to an adjacent T Ga site, and substitute the Ga vacancy.…”
mentioning
confidence: 99%